The Narrative of the ‘new' South Africa: Bearing Witness to the Truth and Reconciliation Commission on its 20th Anniversary - Scott, Heather Ashley (African Studies, 2021)
2015 was a telling year in the ‘new' South Africa's short history. Twenty-one years of democracy, 60 years of the Freedom Charter and the Truth and Reconciliation Commission (TRC) saw its 20th anniversary. This has gone relatively unacknowledged, eclipsed by socio-political and economic turmoil. A struggling economy, rising inequality, unemployment, ‘xenophobia' and democratic, constitutional and parliamentary crises appear to be the way this year will be remembered. South Africa has reached a critical point as its democracy enters adulthood. Twenty years ago the TRC was also such a watershed moment in South African society and politics. I return to this national work of ‘truth', reconciliation, nation-building, healing and remembrance to see what this radical (and radically important) process can teach us about the more ethical (re-)definition of our ‘new' nation(alism). Particularly I address the ‘official' rhetoric and narrative of the ‘new' South Africa it birthed 20 years ago - South Africa as reconciled rainbow nation and progressive constitutional democracy united in the spirit of ‘traditional' pan-African ubuntu - and its (in)appropriability on the lived level (Sauter, 2015:190). I use Antjie Krog, Nosisi Mpolweni and Kopano Ratele's quasi-literary, quasi-academic engagement with the TRC and the ‘unintelligible' truth of an-‘other' in There was this Goat: Investigating the Truth Commission Testimony of Notrose Nobomvu Konile (2009) to do so.